2008
DOI: 10.1021/la802179m
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Models for Anion Distribution: Specific Iodide Binding to Sulfobetaine Micelles

Abstract: The reaction of I (-) with methyl naphthalene-2-sulfonate (MeONs) is accelerated by the micellized sulfobetaine surfactants N-decyl, N-dodecyl, N-tetradecyl, and N-hexadecyl- N, N-dimethylammonio-1-propanesulfonate. Concentrations of micellar-bound I (-) were determined by using ion-selective electrodes (ISE), and capillary electrophoresis. At low concentrations, I (-) incorporation fits Langmuir isotherms and is related to changes in micellar surface potentials. Rate effects of dilute KI are fitted quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 39 publications
3
29
0
3
Order By: Relevance
“…33,34 Initially, the zeta potential of the C 12 TAB micelle was calculated above the CMC 2 of the free surfactant, where the behavior should be closely related to a solution of C 12 TAB without additives. 33,34 Initially, the zeta potential of the C 12 TAB micelle was calculated above the CMC 2 of the free surfactant, where the behavior should be closely related to a solution of C 12 TAB without additives.…”
Section: Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Initially, the zeta potential of the C 12 TAB micelle was calculated above the CMC 2 of the free surfactant, where the behavior should be closely related to a solution of C 12 TAB without additives. 33,34 Initially, the zeta potential of the C 12 TAB micelle was calculated above the CMC 2 of the free surfactant, where the behavior should be closely related to a solution of C 12 TAB without additives.…”
Section: Electrophoresismentioning
confidence: 99%
“…where Z is the viscosity of the medium, f (kR m ) corresponds to Henry's function, k is the Debye-Hu ¨ckel shielding parameter (m À1 ), R m is the radius of C 12 TAB micelle, and e o and e correspond to the vacuum permittivity and the relative permittivity of the solvent. 33,34 Initially, the zeta potential of the C 12 TAB micelle was calculated above the CMC 2 of the free surfactant, where the behavior should be closely related to a solution of C 12 TAB without additives. In order to proceed with the calculation of zeta potential, we adopted the reported radius value (R m ) of the C 12 TAB micelle of 20 Å.…”
Section: Electrophoresismentioning
confidence: 99%
“…Nome and coworkers 6 studied the S N 2 reaction of methyl napthalenesulfonate with iodide in zwitterionic sulfobetaine micelles at varying total iodide concentration. The authors demonstrated that the electrostatic and ion-specific interactions in sulfobetaine micelles become unimportant if the concentration of the reactive iodide ion is high.…”
Section: Reactivity In Micelles a Medium Effects And Compartmentalisa...mentioning
confidence: 99%
“…Understanding the properties of the interface is particularly important in organic materials and natural sand because of its abundance in the environment and its potential to bind inorganic and organic pollutants [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%